If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -6 = 17 + -2x Reorder the terms: -6 + 3x = 17 + -2x Solving -6 + 3x = 17 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. -6 + 3x + 2x = 17 + -2x + 2x Combine like terms: 3x + 2x = 5x -6 + 5x = 17 + -2x + 2x Combine like terms: -2x + 2x = 0 -6 + 5x = 17 + 0 -6 + 5x = 17 Add '6' to each side of the equation. -6 + 6 + 5x = 17 + 6 Combine like terms: -6 + 6 = 0 0 + 5x = 17 + 6 5x = 17 + 6 Combine like terms: 17 + 6 = 23 5x = 23 Divide each side by '5'. x = 4.6 Simplifying x = 4.6
| 3(w-3)=-9 | | 5-8x=115-43x | | -3(t+1)=0 | | 9+3-2y=14 | | x+3y=-25 | | x-3y=-1 | | -45=9(y+2) | | 6a^2+4A+9A+6=0 | | 12x-x^2-18=0 | | -8+6x=10x+16 | | -6-9x=10x+22 | | 1x^2-12x-18=0 | | 0.07x+0.12(8000-x)=700 | | -6y-9=5y+24 | | -7x-9=19 | | 77-3x=2x+17 | | 9=-5x+39 | | 3x+12=82-4x | | p^2+2p-8=(p-2) | | 147-4x=23x+24 | | 11x-7=42 | | 8-8x=42-15x | | y-5=2y+3 | | 6x=64+12x+10 | | 0=-2x^2+3x+0 | | 4x+2=2x+7 | | 2x-5=4x-3 | | 50+5x=6x^2 | | x=5y+.5y+1.25y | | 8k=64 | | H+3=-2 | | bx+ax=c |